Crime in Colombia: More law enforcement or more justice? (2014)
This study considers the effect that judicial and police efficiency exercised on crime in 25 of the 33 political-administrative divisions in Colombia during the period 2000- 2011. Specifically, the study seeks to determine whether the reduction of crime was the result of increases in the cost of crime as a result of the strengthening of the country’s security forces, especially the National Police, or instead was due to the greater efficiency of the penal system resulting from a structural change stemming from Act 906 of 2004. To view this we propose a model of dynamic panel data that not only includes the individual and temporal effects of the variables of interest, but also allows us to understand the inertia in criminal behavior. The results indicate an inverse relationship between the number of crimes and the greater efficiency of the police and judicial action, which is consistent with the evidence reported in other international work. Robustness checks confirmed the validity of the findings.